Changes in industry marketing payments to physicians during the covid-19 pandemic: quasi experimental, difference-in-difference study. Issue 1 (6th September 2022) - Inoue, Kosuke; Figueroa, Jose F; Kondo, Naoki; Tsugawa, Yusuke
Abstract : Objective: To determine changes in industry marketing payments to physicians due to the covid-19 pandemic. Design: Quasi experimental, difference-in-difference study. Data source: US nationwide database of licensed physicians, the National Plan and Provider Enumeration System, which was linked to a database of industry marketing payments made to physicians, Open Payments. Population: All licensed US physicians from 2018 to 2020 and those who received payments from industry. Main outcome measures: Changes in the value and the number of monthly industry payments physician received before (January-February 2020) and during the pandemic (April-December 2020) were assessed, adjusting for physicians' characteristics (gender and specialty). As the control, data for the same months in 2019 were used. Industry payments by type of payments (eg, meals, travel, consulting fees, speaker compensation, honorariums), were also examined. Results: Among 880 589 US physicians included in this study, 267 463 (30.4%) physicians received a total of 4 117 482 non-research payments with $626 million ($710 per physician; £610; €708) in 2020 (40-44% decrease from $1047m in 2018 and $1115m in 2019). Industry payments decreased significantly in the months of the covid-19 pandemic (adjusted change in the value of −48.4%; 95% confidence interval −50.6 to −46.2; P<0.001; and adjusted change in the number of −47.4%, 95% confidence interval −47.7 to −47.1; P<0.001), particularly for meals and travel fees. No evidence was seen of a decrease in the number of industry payments for consulting and honorariums. A similar pattern was observed across physicians' gender and specialty. Conclusions: Industry payments to physicians, particularly those involving physical interactions such as meals and travel, substantially decreased during the pandemic. How such changes affect prescription practices and the quality of clinical practice in the long term should be investigated.